Comparison of the predictive capability of antral follicle count vs. the anti-Müllerian hormone for ovarian response in infertile women - Sun, Xingyu; Xiong, Wang; Liu, Liting; Xiong, Junjun; Liao, Chenlu; Lan, Yunzhu; Li, Feifei; Tao, Shufei; Meng, Muzi; Sun, Chenyu; Mao, Xiguang (Frontiers in Endocrinology, 2022)
Objectives: The study aimed to compare predictive capability of antral follicle count (AFC) vs anti-Müllerian hormone (AMH) for the ovarian response in infertile women and to identify the potential factors that affect retrieved oocytes. Methods: The study enrolled 2585 infertile women who underwent in vitro fertilization/ intracytoplasmic sperm injection (IVF/ICSI) cycles. Spearman correlation were used to investigate the association between retrieved oocytes and AFC. Multiple linear regression analysis was used to investigate the parameters that could influence the number of retrieved oocytes. Results: Spearman correlation and multiple linear regression analysis revealed that the number of retrieved oocytes were positively correlated with AFC（r=0.651, P＜0.001） and AMH (r=0.566, P＜0.001), and negatively correlated with age (r=-0.425, P＜0.001) and protocols selection (r=-0.233 P＜0.001). No significant correlation was found between retrieved oocytes and BMI(P=0.913). ROC analysis revealed that AFC performed better in poor response prediction than AMH, BMI, and age (AUC: 0.916 VS 0.791, 0.575, 0.752). Meanwhile, AFC and AMH had comparable efficacies in predicting high response prediction (AUC= 0.731 and AUC = 0.733, respectively). Conclusions: This study shows that retrieved oocytes were positively correlated with serum AMH and AFC and negatively correlated with age and BMI. AFC had an ideal predictive performance in ovarian response prediction. Further studies are warranted to discover the mechanism of the effects of AFC on the ovarian response in the process of controlled ovarian hyperstimulation (COH).